Insulin and Melatonin Modulates the Histo Architecture, Cellular Biochemistry and Receptor Expression During Injury of Hepatic in Diabetic individuals and its treatment - Muhammad Nabi, Asim Muhammad, Zakia Subhan, Gul Hassan, Nabila Sher Mohammad, Abdul Salam, Sudhair Abbas Bangash, Nabiha Naeem, Irfan Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this research was to examine the effects of exogenous melatonin and insulin on the biochemical, serological, histological, and receptor expression architecture of liver tissues in response to hepatic damage. Study Design: Observational study Place and Duration: This study was carried out at Hayatabad Medical Complex from November 2021 to March 2022 Methods: Total 72 patients of diabetes mellitus had age 19-78 years were presented in this study. All the patients had hepatic injury and admitted to outpatient department. After obtaining informed written consent detailed demographics of enrolled cases were recorded. Patients received melatonin and insulin therapy and continuous follow up was taken. Outcomes among all patients were recorded in terms of effectiveness. SPSS 23.0 was used to analyze all data. Results: Mean age of the patients was 42.13±16.42 years and had mean BMI 28.11±8.38 kg/m2.Most of the patients were from rural areas and were not educated. 45 (62.5%) were married and remaining 27 (37.5%) were not married. Majority patients 50 (69.4%) had diabetes mellitus-2. Other diseases were hypertension, pulmonary disease, respiratory and cardiac disease. As per liver function test, significant increased values were obtained in ALT, AST, ALP, serum cholesterol, LDL, VLD but decrease in HDL level. We found recovery of hepatic injury in 64 (88.9%) cases. Biochemical, cellular structure of liver cells, and the expression pattern of MT1, MT2, and IR receptors were all shown to have significantly recovered and restored. Conclusion: We concluded in this study that combine therapy of melatonin and insulin among diabetic patients of hepatic injury resulted significantly good results in terms of efficacy and disease recovery. Keywords: Diabetes Mellitus, Insulin, Melatonin, Efficacy, Hepatic Injury